Pengaruh Brand Ambassador Dan Brand Image Terhadap Minat Beli Yang Berdampak Pada Keputusan Pembelian - Annung Purwati; Mega Mirasaputri Cahyanti (IQTISHADUNA: Jurnal Ilmiah Ekonomi Kita, 2022)
This research aims to show the influence of brand ambassadors and brand image on buying interest and their impact on purchasing decisions. This study uses a quantitative approach. The research population is Scarlett consumers, whose total is not known with certainty. Sampling using purposive sampling technique and obtained 73 samples. The data analysis technique uses path analysis. The results showed that the brand ambassador did not affect buying interest. The brand image has a positive and significant influence on buying interest. The purchase intention has a positive and significant effect on purchasing decisions. The brand ambassador has a positive and significant effect on purchasing decisions. The brand image has no significant effect on purchasing decisions. The purchase intention cannot mediate the relationship between brand ambassadors and purchase decisions. The purchase intention can mediate the relationship between brand image and purchasing decisions. Companies can use this research in deciding policies and formulating strategies for maintaining a good brand image from consumer perceptions and using brand ambassadors to promote products.